Towards cultural translation of websites: a large-scale study of Australian, Chinese, and Saudi Arabian design preferences - Alexander, R.; Thompson, Nik; Murray, D. (Brill, 2016)
Since websites are developed and maintained by different cultures, web page design may be influenced by the originating culture. This study examines the usage of design attributes between Australian, Chinese, and Saudi Arabian cultures. This study used automated and manual techniques to investigate design attributes including layout, navigation, links, multimedia, visual representation, colour, and text. Significant differences were found in each of the listed design attributes, suggesting that different interfaces may be needed for successful communication with different cultural groups. The results of this study confirm and extend prior research and anthropological models. The contribution of this study is the scale (460 websites in total) and breadth (seven design attributes) of the research. It also provides revised insights into culture and website design and the concept of cultural translation of web content.